The Impact of LDR, NIM, and Car on the Stock Price Performance of State-Owned Bank: A Study for the 2015-2024 Period - Muhammad Thirofa Zain Ma'ruf; Muhammad Habib; Maiyaliza Maiyaliza (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to examine the partial impact of Loan to Deposit Ratio (LDR), Net Interest Margin (NIM), and Capital Adequacy Ratio (CAR) on the stock price performance of state-owned banks (SOEs) in Indonesia during the 2015–2024 period. The research employs a quantitative approach using multiple linear regression analysis based on secondary data from the financial statements of four SOEs listed on the Indonesia Stock Exchange. The results show that the Loan to Deposit Ratio (LDR) has a negative but insignificant effect on stock prices, indicating that liquidity efficiency does not directly influence investor assessments of bank performance. The Net Interest Margin (NIM) has a significant negative effect, suggesting that a higher interest margin may reflect increased credit risk or reduced competitiveness, which is perceived negatively by the market. Meanwhile, the Capital Adequacy Ratio (CAR) has a significant positive effect, demonstrating that stronger capital adequacy increases investor confidence and supports higher stock valuations. These findings imply that not all financial ratios consistently affect stock prices and that investor perceptions depend on broader market conditions and bank-specific strategies.